1967
DOI: 10.1177/15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Demonstration of Dehydrogenase Activity With a New Osmiophilic Ditetrazolium Salt (Tc-Nbt)

Abstract: Dissatisfaction with the degree of contrast produced by currently available tetrazolium salts in electron microscopy of the dehydrogenases stimulated us to design and prepare an osmiophilic ditetrazolium salt (TC-NBT)3 containing thiocarbamyl groups in innocuous positions of the nitro-BT molecule. The new reagent has the same favorable properties as nitro-BT for light microscopy and, in addition, is convertible to osmium black when tissue sections containing the diformazan are exposed to osmium tetroxide vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1967
1967
1984
1984

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The existence of active and nonactive mitochondria in the same cell was described by Seligman et al (8) for animal tissues and was also found in cells of normal root tips (Fig. 2).…”
Section: Discussionsupporting
confidence: 82%
“…The existence of active and nonactive mitochondria in the same cell was described by Seligman et al (8) for animal tissues and was also found in cells of normal root tips (Fig. 2).…”
Section: Discussionsupporting
confidence: 82%
“…It was of interest to determine whether succinic dehydrogenase, which ordinarily donates electrons via cytochrome b to nitro-containing tetrazolium salts (14), had a similar or opposite localization for its electron-donating activity as compared to cytochrome oxidase. However, doubt has been cast on our earlier interpretations of the observation of dense, contracted mitochondria in dehydrogenase preparations of fresh rat heart made with an osmiophilicditetrazolium salt (TC-NBT) (21). 4 Haydon 4 Material on the market being sold as TC-NBT by Nutritional Biochemicals Corporation, Cleveland, O., is not osmiophilic and melts 30 0 C lower than our material.…”
Section: Discussionmentioning
confidence: 78%
“…Unstained sections were also studied. This procedure has also been used to reveal underlying ultrastructure for other enzymatic methods (5,21,22).…”
mentioning
confidence: 99%